2020
DOI: 10.1029/2019gb006446
|View full text |Cite
|
Sign up to set email alerts
|

Biogeochemical Connectivity Between Freshwater Ecosystems beneath the West Antarctic Ice Sheet and the Sub‐Ice Marine Environment

Abstract: Although subglacial aquatic environments are widespread beneath the Antarctic ice sheet, subglacial biogeochemistry is not well understood, and the contribution of subglacial water to coastal ocean carbon and nutrient cycling remains poorly constrained. The Whillans Subglacial Lake (SLW) ecosystem is upstream from West Antarctica's Gould‐Siple Coast ~800 m beneath the surface of the Whillans Ice Stream. SLW hosts an active microbial ecosystem and is part of an active hydrological system that drains into the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 100 publications
3
48
0
Order By: Relevance
“…The WGZ sedimentary system is composed of material influenced by glacial and subglaciofluvial processes (e.g., Christianson et al, 2013; Horgan, Alley, et al, 2013; Horgan, Christianson, et al, 2013; Vick‐Majors et al, 2020). In a sub‐ice shelf setting, the proportion of preaged carbon transported from the continent (allochthonous material) is present in much higher proportion than carbon input from the marine environment (autochthonous material), with ages of these components reflecting the dynamic processes occurring before deposition (Subt et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The WGZ sedimentary system is composed of material influenced by glacial and subglaciofluvial processes (e.g., Christianson et al, 2013; Horgan, Alley, et al, 2013; Horgan, Christianson, et al, 2013; Vick‐Majors et al, 2020). In a sub‐ice shelf setting, the proportion of preaged carbon transported from the continent (allochthonous material) is present in much higher proportion than carbon input from the marine environment (autochthonous material), with ages of these components reflecting the dynamic processes occurring before deposition (Subt et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The drill water and SLW water column (Vick-Majors et al 2020) contained FDOM; however, the FDOM in water collected from the clean access ports and borehole water was distinct from that found in the SLW water column samples (Fig. 2).…”
Section: Discussionmentioning
confidence: 94%
“…CC-BY-NC 4.0 International license available under a (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity. It is made The copyright holder for this preprint this version posted March 2, 2021. ; https://doi.org/10.1101/2021.03.02.433610 doi: bioRxiv preprint to play an important role not only in the biogeochemistry of basal ice but also downstream terrestrial, freshwater, and marine environments which receive seasonal discharges of basal meltwater (Wadham et al, 2010;Barker et al, 2018;Hopwood et al, 2019;Vick-Majors et al, 2020). Indeed, basal meltwater is one of the largest sources of labile dissolved organic carbon and iron to coastal oceans adjacent to glaciated watersheds (Hood et al, 2009;Bhatia et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This view began to change around the turn of the century after mounting evidence from several pioneering studies revealed microorganisms are not only abundant in subglacial environments but actively participate in weathering processes (Sharp et al ., 1999; Skidmore et al ., 2000; Tranter et al ., 2002, 2005; Sheridan et al ., 2003; Miteva et al ., 2004; Yung et al ., 2007). The metabolic activity of basal ice microorganisms is now thought to play an important role not only in the biogeochemistry of basal ice but also downstream terrestrial, freshwater, and marine environments which receive seasonal discharges of basal meltwater (Wadham et al ., 2010; Barker et al ., 2018; Hopwood et al ., 2019; Vick-Majors et al ., 2020). Indeed, basal meltwater is one of the largest sources of labile dissolved organic carbon and iron to coastal oceans adjacent to glaciated watersheds (Hood et al ., 2009; Bhatia et al ., 2013).…”
Section: Introductionmentioning
confidence: 99%